2006
DOI: 10.1161/circulationaha.105.590232
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evidence for Nitric Oxide–Mediated Calcium-Activated Potassium-Channel Activation During Human Endotoxemia

Abstract: Background-During septic shock, the vasoconstrictor response to norepinephrine is seriously blunted. Animal experiments suggest that hyperpolarization of smooth muscle cells by opening of potassium (K) channels underlies this phenomenon. In the present study, we examined whether K-channel blockers and/or nitric oxide (NO) synthase inhibition could restore norepinephrine sensitivity during experimental human endotoxemia. Methods and Results-Volunteers received 2 ng/kg Escherichia coli endotoxin intravenously. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 36 publications
1
41
3
Order By: Relevance
“…12 In a previous phase 1 study, constant concentration increases of hepcidin after increasing doses of lexaptepid from 0.3 to 4.8 mg/kg indicated that the administration of lexaptepid did not induce hepcidin production by itself. 14 In addition, hepcidin production may have been influenced by the major changes in serum iron as observed throughout the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In a previous phase 1 study, constant concentration increases of hepcidin after increasing doses of lexaptepid from 0.3 to 4.8 mg/kg indicated that the administration of lexaptepid did not induce hepcidin production by itself. 14 In addition, hepcidin production may have been influenced by the major changes in serum iron as observed throughout the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In a first-in-human trial, lexaptepid was well tolerated and effective in elevating serum iron. 14 The primary aim was to investigate the effectiveness of lexaptepid in preventing the serum iron decrease observed during systemic inflammation in healthy volunteers. The secondary objective was to assess the effects of lexaptepid on the innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The patients were recruited by their physicians during outpatient clinic visits (all in Radboud University Nijmegen Medical Centre, Nijmegen, The Netherlands, except for the thalassemia major patients, who were in Ospedale Sant'Eugenio, Rome, Italy). Endotoxemia samples from volunteers injected with lipopolysaccharide were selected from a human endotoxemia project (10 ). Written informed consent was obtained from all study participants, according to the Declaration of Helsinki.…”
Section: Materials and Methods Study Participantsmentioning
confidence: 99%
“…We collected samples randomly between December 2005 and June 2006, at no specified time of day, except from the endotoxemia patients, from whom samples were collected according to a tight time schedule (10,13 ). Urine and blood samples were centrifuged immediately after collection, divided into aliquots to avoid multiple freezethaw cycles, and stored at Ϫ80°C.…”
Section: Materials and Methods Study Participantsmentioning
confidence: 99%
“…Maxi-K channel dysfunction caused either by genetic ablation of either channel subunit or by the use of selective channel inhibitors leads to increased tone in vascular, corpus cavernosum, and detrusor smooth muscles (Suarez-Kurtz et al, 1991;DeFarias et al, 1996;Brenner et al, 2000;Garcia and Kaczorowski, 2001;Meredith et al, 2004;Thorneloe et al, 2005;Werner et al, 2005Werner et al, , 2008Brown et al, 2008), and Maxi-K channel knockout mice display hypertension (Brenner et al, 2000;Plü ger et al, 2000;Sausbier et al, 2005), erectile dysfunction (Werner et al, 2005), and overactive bladder/incontinence (Meredith et al, 2004). Maxi-K channels appear to mediate indirectly the relaxant effects of a number of vasodilators, including nitric oxide, and recent data suggest that attenuated vasoconstrictor response to norepinephrine during experimental human endotoxemia is due to nitric oxide-mediated activation of Maxi-K channels in the vascular wall (Pickkers et al, 2006). Maxi-K channels are major modulators of bladder function by regulating spontaneous and nerve-evoked contractions, and overactivity of urinary bladder smooth muscle causes urge incontinence (Herrera et al, 2005;Thorneloe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%